2021
DOI: 10.1021/jacs.1c04051
|View full text |Cite
|
Sign up to set email alerts
|

Ynamides as Three-Atom Components in Cycloadditions: An Unexplored Chemical Reaction Space

Abstract: While 1,3-dipolar cycloadditions have appeared to be a fertile area for research, as attested by the numerous synthetic transformations and resulting applications that have been developed during the past 60 years, the use of neutral three-atom components (TACs) in (3+2) cycloadditions remains comparatively sparse. Neutral TACs, however, have great synthetic potential given that their reaction with a π system can produce zwitterionic cycloadducts that may be manipulated for further chemistry. We report herein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Although [3+2] cycloaddition reactions of alkynes with 1,3-dipolars are common, the use of neutral three-atom components (TACs) remains comparatively sparse . In our work, the alkynal was unprecedentedly used as a neutral three-atom component to engage [3+2] cycloaddition with a π-system, affording the fused furans.…”
Section: Resultsmentioning
confidence: 99%
“…Although [3+2] cycloaddition reactions of alkynes with 1,3-dipolars are common, the use of neutral three-atom components (TACs) remains comparatively sparse . In our work, the alkynal was unprecedentedly used as a neutral three-atom component to engage [3+2] cycloaddition with a π-system, affording the fused furans.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, this (3+2) process was tolerant of all types of alkynyl groups that were accessed, and presents an alkyne scope noticeably larger than that found in the case of ynamides. 20 A variety of substrates possessing a three, four and fivemembered linker were synthesized, many promoting the yne-alkynyl sulfide (3+2) cycloaddition (Table 2, Part B). Exchanging the model ether linker by a sulfonamide or a malonate group led to moderate to good yields of the corresponding thiophenes 10u and 10w.…”
Section: Table 1 Exploration and Optimization Of Alkyl Alkynyl Sulfid...mentioning
confidence: 99%
“…Recently, our group reported that ynamides 7 -being N-C-C neutral TACs -react intramolecularly with alkynes 1 to produce a wide variety of polycyclic fused pyrroles via the postulated intermediacy of a (3+2) pyrrolium ylide cycloadduct 6. 20 It was observed that all ynamides accessed -derived from carbamates, urea, sulfonamide and sulfamides -cleanly displayed a 1,2-migration of the electron withdrawing group (EWG) in this process to produce 2-EWG substituted pyrroles (Figure 1, Path A). This reliable reactivity was used as a basis to experimentally and theoretically investigate the nature of the unprecedented (3+2) cycloaddition step.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of neutral N-alkynyl TACs, the formation of the key pyrrolium ylide of interest can be considered to some extent as tied to the EWG 1,2-migratory outcome, a process that was calculated to have a low energy barrier (< 5 kcal mol À 1 ). [20] In order to study the synthetic potential of the elusive heteroarylium ylides 6 in further details, a neutral TAC easy to access, and more stable under diverse structural modifications would be required. Although various heteroatomsubstituted alkynes have been synthesized in the past, alkynyl sulfides 8 were found to best fit these criteria.…”
Section: Introductionmentioning
confidence: 99%